REDISCOVERED OF GNETUM GNEMON VAR. TENERUM MARKGR. IN KALIMANTAN - Astuti, Inggit Puji; Mar'atus, Saniyatun; Witono, Joko Ridho (Perhimpunan Biologi Indonesia, 2016)
SHORT COMMUNICATIONRediscovered of Gnetum gnemon var. tenerum Markgr. in Kalimantan